Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.7717/peerj.9140
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive inhibitory effects of levonorgestrel, quinestrol, and EP-1 in Brandt’s vole (Lasiopodomys brandtii)

Abstract: Background Rodent pests can inflict devastating impacts on agriculture and the environment, leading to significant economic damage associated with their high species diversity, reproductive rates and adaptability. Fertility control methods could indirectly control rodent pest populations as well as limit ecological consequences and environmental concerns caused by lethal chemical poisons. Brandt’s voles, which are common rodent pests found in the grasslands of middle-eastern Inner Mongolia, eastern regions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 68 publications
2
17
0
Order By: Relevance
“…2017; Shi et al . 2020). Reproductive organs of males, sperm production, and sperm motility were all negatively affected by both hormones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2017; Shi et al . 2020). Reproductive organs of males, sperm production, and sperm motility were all negatively affected by both hormones.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast with studies in R. nitidius (Liu et al 2013) and Brandt's voles (Zhao et al 2007) which showed that quinestrol did not reduce the weight of the uterus or change its morphology. Edema in the uterus of treated animals has been suggested to be due to increases in estradiol and progesterone level and prolongation of estrogenic activity which results in swelling of the uterus (Su et al 2017;Shi et al 2020). Reproductive organs of males, sperm production, and sperm motility were all negatively affected by both hormones.…”
Section: Discussionmentioning
confidence: 99%
“… 2013 ; Zhang 2015 ; Shi et al . 2020 ). Fertility control does not immediately lower a population, but it prevents the build‐up of population eruptions (Stenseth et al .…”
Section: Introductionmentioning
confidence: 99%
“…Too little is known about conservation agriculture and the positive or negative effects of such practices on pest rodent population dynamics. New management approaches are on the horizon. One example is fertility control of rodent pests 104–106 . Another, although controversial, 107 is synthetic gene drive technology that may provide an opportunity to substantially influence the sex ratio of a rodent population 108 .…”
Section: Recommendations For the Way Forwardmentioning
confidence: 99%